2020
DOI: 10.1055/a-1176-1937
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between Cistus L. (Sub-) Species (Cistaceae) Using NMR Metabolic Fingerprinting

Abstract: The genus Cistus is taxonomically complex, as taxonomic classification of individual species based on morphological criteria is often difficult and ambiguous. However, specific species contain valuable natural products, especially terpenoids and polyphenols, which exert various biological effects and might therefore be used for treatment of a broad array of disorders. Hence, a fast and reliable method for clear identification of different Cistus (sub-) species is required. Approaches for analysis of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies to date recognize between 16 and 28 different species belonging to the genus Cistus, highlighting the intraspecific conflicts underlying their classification [7]; furthermore, there are 31 Cistus species currently listed in the Euro+Med PlantBase [8]. According to their ethnobotanical use, previous scientific studies, and ecological relevance, the eight most relevant identified species that make up the genus are Cistus albidus L., Cistus creticus L., Cistus incanus L., Cistus crispus L., Cistus ladanifer L., Cistus monspeliensis L., Cistus parviflorus Lam., and Cistus salviifolius L. [9].…”
Section: Plants Of the Genus Cistusmentioning
confidence: 99%
“…Studies to date recognize between 16 and 28 different species belonging to the genus Cistus, highlighting the intraspecific conflicts underlying their classification [7]; furthermore, there are 31 Cistus species currently listed in the Euro+Med PlantBase [8]. According to their ethnobotanical use, previous scientific studies, and ecological relevance, the eight most relevant identified species that make up the genus are Cistus albidus L., Cistus creticus L., Cistus incanus L., Cistus crispus L., Cistus ladanifer L., Cistus monspeliensis L., Cistus parviflorus Lam., and Cistus salviifolius L. [9].…”
Section: Plants Of the Genus Cistusmentioning
confidence: 99%
“…The present paper, is a new contribution to the nomenclature in Cistaceae (see, e.g., Ferrer-Gallego & Laguna 2012;Ferrer-Gallego & al. 2013a, 2013b, 2020Ferrer-Gallego 2015a, 2015bFerrer-Gallego & Boisset 2015), and the name Cistus ×canescens Sweet, pro species is typified to contribute to the stability of the nomenclature.…”
Section: Introductionmentioning
confidence: 99%